Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð´Ð¸Ð¼ÐµÐºÑÐ¸Ð´Ð° Ð½Ð° Ñ„ÑƒÐ½ÐºÑ†Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ñ‹Ðµ Ñ…Ð°Ñ€Ð°ÐºÑ‚ÐµÑ€Ð¸ÑÑ‚Ð¸ÐºÐ¸ Ñ‚ÐµÑÑ‚Ð¸ÐºÑƒÐ»ÑÑ€Ð½Ð¾Ð¹ Ñ‚ÐºÐ°Ð½Ð¸ ÐºÑ€Ð¾Ð»Ð¸ÐºÐ¾Ð² - Chadaev, V. E. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2009)
The effect of dimethyl sulfoxideÂ cryoprotectant on functional characteristics of rabbit testicular tissue has been studied. It has been established that the low concentrations of dimexide strengthen the effect of steroidogenesis stimulators, but the higher ones inhibit.